1999
DOI: 10.1007/s004180050333
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase II and H + -ATPase in osteoclasts of four osteopetrotic mutations in the rat

Abstract: Osteopetrosis in laboratory animals is a metabolic bone disease characterized by increased skeletal mass. It is inherited as an autosomal recessive and results from a defect in the development and/or function of osteoclasts. We studied two enzymes essential for bone resorption, carbonic anhydrase II isoenzyme (CA II) and H+ -ATPase, in osteoclasts from four osteopetrotic mutations in the rat; namely incisors-absent (ia), osteopetrosis (op), toothless (tl), and microphthalmia (mib), to test the hypothesis that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Frattini et al (17) have reported that a defect in the T cell immune regulator 1 (TCIRG1) subunit of the vacuolar proton pump is responsible for a subset of human autosomal recessive (malignant) osteopetrosis. However, Sundquist et al (18) have shown that H + ‐ATPase was present in osteoclasts isolated from normal and mutant animals from op stock and that the enzyme was concentrated in the ruffled border region of the cells. Although they were not able to assess the proton pumping ability of osteoclasts, they reported that proton pumping ability in op kidney tissue was elevated when compared with normal littermates (NLMs).…”
Section: Discussionmentioning
confidence: 99%
“…Frattini et al (17) have reported that a defect in the T cell immune regulator 1 (TCIRG1) subunit of the vacuolar proton pump is responsible for a subset of human autosomal recessive (malignant) osteopetrosis. However, Sundquist et al (18) have shown that H + ‐ATPase was present in osteoclasts isolated from normal and mutant animals from op stock and that the enzyme was concentrated in the ruffled border region of the cells. Although they were not able to assess the proton pumping ability of osteoclasts, they reported that proton pumping ability in op kidney tissue was elevated when compared with normal littermates (NLMs).…”
Section: Discussionmentioning
confidence: 99%
“…Diseases that affect bone mass and the normal metabolism of bone can impact on tooth formation and the maintenance of tooth support through the alveolar bone. Thus, defects in genes regulating osteoclast formation and activity often lead to impaired tooth eruption, as observed in op/op mice (265) and core binding factor a1-null mice (122) and in osteopetrotic mutations found in rats (222), such as incisors-absent (ia), osteopetrosis (op), toothless (tl), and microphthalmia (mib). Similarly, defects in tooth development would be expected in osteoprotegerin ligand (123) and nuclear factor kB (65) knockout mice and mice over-expressing osteoprotegerin (212).…”
Section: Pathologies Affecting Alveolar Bonementioning
confidence: 99%
“…Supporting this conclusion are results from mice lacking carbonic anhydrase (CA) II. Osteoclasts lacking CA II are incapable of acidifying the resorptive microenvironment (23,29,30), and mice deficient in CA II are osteopetrotic and develop arterial calcification (31,32). Collectively, findings from these studies suggest that reduced numbers of functional osteoclasts enable mineral deposition by arterial osteoblast-like cells to occur unopposed.…”
Section: Osteopetrotic Mice Exhibit Augmented Arterial Calcificationmentioning
confidence: 99%